Impact of Biphasic Calcium Phosphate mixed with injectable platelet rich fibrin (i-PRF) on bone density in surgically created bone defects in a sheep animal model (A Radiographic Assessment) - Junayna H. Ali; Rayan S. Hamed (University of Mosul, College of Dentistry, 2023)
Aims: To assess bone density means with Biphasic calcium phosphate alone or mixed with injectable platelet-rich fibrin in bone defects created surgically in sheep's tibia / radius using standard radiographic assessment. Materials and Methods: Three bony defects of 4mm full and 7 mm in diameter were created in every tibias/radius of five sheep. The defects were stuffed within the following order: from a proximal to distal orientation; 1st defect was full of biphasic calcium phosphate alone, the second was left empty to be filled by physiological clot and also the third with i-PRF mixed with BCP and covered with absorbable collagen membrane for tissue guiding and then sutured. Densitometric analysis of bone defects was made to measure density of bone at four-time intervals (two, four, six and eight weeks) post-surgically. Results: Densitometric analysis results showed a major distinction within the BCP+i-PRF group and BCP group compared with the control one and at all-time intervals with the best density being in the 1st group followed by the BCP alone group and least in the control group. Conclusions: BCP and i-PRF, both of them increased and sustained bone density (synergistic effect) throughout the study period as revealed by densitometric data.